2019
DOI: 10.3892/ijo.2019.4911
|View full text |Cite
|
Sign up to set email alerts
|

A FXYD5/TGF‑β/SMAD positive feedback loop drives epithelial‑to‑mesenchymal transition and promotes tumor growth and metastasis in ovarian cancer

Abstract: Epithelial ovarian cancer is aggressive and lacks effective prognostic indicators or therapeutic targets. In the present study, using immunohistochemistry and bioinformatics analysis on ovarian cancer tissue data from The Obstetrics and Gynecology Hospital of Fudan University and The Cancer Genome Atlas database, it was identified that FXYD domain-containing ion transport regulator 5 (FXYD5) expression was upregulated in the SKOV3-IP cell line compared with its parental cell line, SKOV3, and in ovarian cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…Hence, our results in OTSCC cells strengthens the previous findings for the tumour-promoting role of FXYD5 in other cancers. Breast cancer cells overexpressing FXYD5 metastasize more compared to controls 36 and similar findings were shown in ovarian cancer 58 . FXYD5 also disperses the TβR1 complex leading to enhanced TGF-β signalling and SMAD3/4 activation, which in turn upregulates FXYD5 gene expression in ovarian cancer 58 .…”
Section: Discussionsupporting
confidence: 73%
“…Hence, our results in OTSCC cells strengthens the previous findings for the tumour-promoting role of FXYD5 in other cancers. Breast cancer cells overexpressing FXYD5 metastasize more compared to controls 36 and similar findings were shown in ovarian cancer 58 . FXYD5 also disperses the TβR1 complex leading to enhanced TGF-β signalling and SMAD3/4 activation, which in turn upregulates FXYD5 gene expression in ovarian cancer 58 .…”
Section: Discussionsupporting
confidence: 73%
“…Informed consent was obtained from all patients prior to the study. Immunohistochemical staining was conducted as described previously [20]. Immunostaining scores of POSTN in stromal and tumor components were assessed using a scoring system encompassing staining intensity (0 = none, 1 = weak, 2 = moderate, 3 = strong) and positivity percentage (0 ≤5%, 1 = 5-25%, 2 = 26-50%, 3 = 51-75%, 4 = 76-100%); the product of the scores produced a final score ranging from 0 to 12.…”
Section: Immunochemistrymentioning
confidence: 99%
“…The high expression of TGF-β3 is associated with poor prognosis of high-grade serous carcinoma, and it is a potential indicator for the evaluation of ovarian cancer prognosis (57). Recent studies have reported that in ovarian cancer stem cells, inhibition of TGF-β/SMAD pathway activation can further inhibit EMT (58)(59)(60). In 2012, Kulbe et al (61) first described the 'TNF' network in the ovarian cancer microenvironment.…”
Section: Cell Signaling and Exosome-mediated Tumor Immune Microenviromentioning
confidence: 99%